Studies on Seed Germination and Seedling Growth of Bhimal (Grewia optiva Drummond.) in Central India - Tewari, R.K.; Bajpai, C.K.; Gupta, Astha (Indian Journal of Agroforestry, 2020)
Bhimal (Grewia optiva), a common MPTs of Himalayan foot hills on crop lands has recently been introduced in central India. One Year old seeds were collected from Indian Grassland and Fodder Research Institute, Jhansi and subjected to presowing seed treatments. Observations indicated that acid treatment (ConC. H2S04) for 15 min. and then soaking in water for 24 hrs gave maximum 44% germination, which was significantly higher than other treatments. The treatment produced maximum seedling growth and biomass yield followed by 24 hrs seed soaking in ordinary water treatment. Maximum 1.32 cm day-1 increment in plant height and 0.10 cm day-1Â in collar diameter were recorded under acid treatment. Seedlings produced 4.76 to 7.01 g plant-1 biomass within120 days of seed sowing.